Rapaz-do-cavalo-branco: o mito milenarista/messiânico no contexto d’A Pedra do Reino, de Ariano Suassuna - Oliveira, Duilio da Silva (2019)
This dissertation aims to present a study on millenarianism/messianism from the character White Horse-Boy, Sinésio, present in the Romance d’A Pedra do Reino e o Príncipe do Sangue do Vai-e-volta of Ariano Suassuna. For this, we start with a brief textual analysis from Paul Ricoeur 's hermeneutics, entering the genre to which the work presents itself until we reach the millenarian/messianic myth. From these eschatological currents, we see the role of Sinésio in the context to which he finds himself, seen as a hopeful light in the face of crimes and agitations, a new Dom Sebastião, who arrives/returns to Taperoá after some years of the tragic sticking of his father: Dom Pedro Sebastião Garcia-Barreto. In this way, the white horse Donzel becomes a sebastic messiah for part of that population, universalizing the facts that occurred in the backwoods of the old cariris. The last stage of the work is to see if the realization of the messianic prophecy of a renewed time, earthly paradise, actually happens. Thus we will cite other representatives of Christian mystique who, like Sinésio, are heroic beings - knights - who had the goal of transforming the world into a new face completely geared to the ideals of Christendom.